Effectiveness of ECOWAS in Countering Coups in West Africa: A Case Study of Niger Republic - Abdulrahman, Barau Yusuf; Taiwo, Abbas Ayodele; Nazifi, Shehu Imam (Kashere Journal of Politics and International Relations, 2025)
This paper examines the effectiveness of the Economic Community of West African States (ECOWAS) in deterring and responding to coups d'état, focusing on the 2023 military takeover in Niger Republic. It analyses both the strengths and weaknesses of ECOWAS's response to the coup while proposing key areas for improvement in the organisation's efforts to promote regional democratic stability. Employing a liberalist theoretical framework and utilising secondary data sources, the study finds that ECOWAS’ sanctions on Niger Republic established a regional precedent, influencing actions by the West African Economic and Monetary Union (WAEMU) and sending a message of deterrence. However, inconsistencies in applying sanctions hampered its effectiveness in restoring President Bazoum to power. Additionally, ECOWAS faced challenges in securing unanimous support for military intervention. These weaknesses significantly hampered ECOWAS' ability to achieve its goals in Niger Republic. To strengthen its response to coups, the paper recommends that ECOWAS must ensure uniform and robust enforcement of sanctions and other measures against all coup perpetrators in the region. It further recommends prioritising preventive diplomacy by proactively identifying and addressing potential conflicts before they erupt into coups, promoting economic development by supporting initiatives that tackle poverty and create opportunities, reducing the appeal of military intervention, and collaborating with member states to strengthen democratic institutions, transparency, and accountability. By implementing these multi-pronged approaches, ECOWAS can become a more effective force for lasting stability and democracy in West Africa